Anti-Colonial Struggles and Decolonization: Strategies for Departure from Imperial Powers in Africa - Alaye, Adekunle (Acta Universitatis Danubius. Juridica, 2024)
This paper examines the multifaceted landscape of anti-colonial struggles and decolonization in Africa, focusing on the diverse strategies employed by African nations to achieve independence and sovereignty from imperial powers. Drawing upon historical analysis and contemporary scholarship, the study underscores the agency and resilience of African peoples in navigating the complexities of colonial domination and forging paths toward liberation. It explores a spectrum of strategies, ranging from armed resistance and political mobilization to diplomatic negotiations and grassroots movements, highlighting the interconnectedness of local, regional, and global dynamics in shaping the decolonization process. Through a comparative lens, the paper elucidates the nuanced approaches adopted by different African countries, considering factors such as colonial legacies, socio-economic conditions, and geopolitical pressures. Furthermore, it interrogates the enduring legacies of colonialism and the ongoing challenges of neocolonialism, emphasizing the imperative of continued solidarity and collective action in advancing the cause of African liberation. Ultimately, this research contributes to a deeper understanding of the complexities and trajectories of anti-colonial struggles in Africa, offering insights into the diverse strategies employed to confront and transcend the legacy of imperial domination.